Answer:
[tex]{x,y} = {2,-3}[/tex]
Step-by-step explanation:
[tex]x - y = 5 \\\\[2] 3x - 2y = 12[/tex] <----------- Linear equations given
Graphic Representation of the Equations: PICTURE
[tex]y + x = 5 \\-2y + 3x = 12[/tex]
Solve by Substitution :
// Solve equation [1] for the variable [tex]x[/tex]
[tex][1] x = y + 5[/tex]
// Plug this in for variable [tex]x[/tex] in equation[tex][2][/tex]
[tex][2] 3*(y +5) - 2y = 12 \\ [2] y = -3[/tex]
// Solve equation [tex][2][/tex] for the variable [tex]y[/tex]
[tex][2] y = - 3[/tex]
// By now we know this much :
[tex]x = y+5 \\ y = -3[/tex]
// Use the y value to solve for [tex]x[/tex]
[tex]x = (-3)+5 = 2[/tex]
Solution :
[tex]{x,y} = {2,-3}[/tex]